Posteromedial Meniscocapsular Lesions Increase Tibiofemoral Joint Laxity With Anterior Cruciate Ligament Deficiency, and Their Repair Reduces Laxity - Stephen,JM; Halewood,C; Kittl,C; Bollen,SR; Williams,A; Amis,AA (American Journal of Sports Medicine, 2016)
Background:Injury to the posteromedial meniscocapsular junction has been identified after anterior cruciate ligament (ACL) rupture; however, there is a lack of objective evidence investigating how this affects knee kinematics or whether increased laxity can be restored by repair. Such injury is often overlooked at surgery, with possible compromise to results.Hypotheses:(1) Sectioning the posteromedial meniscocapsular junction in an ACL-deficient knee will result in increased anterior tibial translation and rotation. (2) Isolated ACL reconstruction in the presence of a posteromedial meniscocapsular junction lesion will not restore intact knee laxity. (3) Repair of the posteromedial capsule at the time of ACL reconstruction will reduce tibial translation and rotation to normal. (4) These changes will be clinically detectable.Study Design:Controlled laboratory study.Methods:Nine cadaveric knees were mounted in a test rig where knee kinematics were recorded from 0° to 100° of flexion by use of an optical tracking system. Measurements were recorded with the following loads: 90-N anterior-posterior tibial forces, 5-N·m internal-external tibial rotation torques, and combined 90-N anterior force and 5-N·m external rotation torque. Manual Rolimeter readings of anterior translation were taken at 30° and 90°. The knees were tested in the following conditions: intact, ACL deficient, ACL deficient and posteromedial meniscocapsular junction sectioned, ACL deficient and posteromedial meniscocapsular junction repaired, ACL patellar tendon reconstruction with posteromedial meniscocapsular junction repair, and ACL reconstructed and capsular lesion re-created. Statistical analysis used repeated-measures analysis of variance and post hoc paired t tests with Bonferroni correction.Results:Tibial anterior translation and external rotation were both significantly increased compared with the ACL-deficient knee after posterior meniscocapsular sectioning (P <